2020
DOI: 10.3390/microorganisms8010074
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Co-Occurrence of Mycotoxins in Cereal-Based Feed and Food

Abstract: Dietary (co)-exposure to mycotoxins is associated with human and animal health concerns as well as economic losses. This study aims to give a data-based insight from the scientific literature on the (co-)occurrence of mycotoxins (i.e., parent and modified forms) in European core cereals, and to estimate potential patterns of co-exposure in humans and animals. Mycotoxins were mainly reported in wheat and maize showing the highest concentrations of fumonisins (FBs), deoxynivalenol (DON), aflatoxins (AFs), and ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 18 publications
(17 reference statements)
2
69
0
1
Order By: Relevance
“…In barley, fumonisins were found by Beccari et al [ 28 ] in 2% of samples, with concentrations at the levels of 156 μg kg −1 for FB1 and 65 μg kg −1 for FB2. In oats, fumonisins have only seldom been reported [ 29 ]. Our results are in a good agreement with these findings and confirmed that fumonisins do not pose a substantial risk for hulless barley and oats.…”
Section: Discussionmentioning
confidence: 99%
“…In barley, fumonisins were found by Beccari et al [ 28 ] in 2% of samples, with concentrations at the levels of 156 μg kg −1 for FB1 and 65 μg kg −1 for FB2. In oats, fumonisins have only seldom been reported [ 29 ]. Our results are in a good agreement with these findings and confirmed that fumonisins do not pose a substantial risk for hulless barley and oats.…”
Section: Discussionmentioning
confidence: 99%
“…Although rice is not the high-risk commodity for AFs contamination, AFB 1 besides other mycotoxins have been found in rice from China, Egypt, India, Iran, Malaysia, Nepal, Pakistan, the Philippines, United Kingdom, and the United States [42], [54]. Palumbo et al [55] found that AFs in rice of the highest mean concentrations of AFB1 n = 124; mean 3.1-3.3 μg/kg; max: 91.7 μg/kg. In our results, the total AFs were detected in some foods above the acceptable limits set by the European Union 4 ug/kg could be attributed to some suitable factors such as pH, nutrient composition, moisture content water activity, as well as external factors as temperature, relative humidity, soil properties, insects, and rodents attack [56], [57].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of the Joint FAO/WHO Expert Committee on Food Additives [ 63 , 64 , 65 ] together with recent papers that analyzed data (500,000 analyses) from EFSA and large global surveys available in the literature and in international databases suggest mycotoxin prevalence of >25% as stated by the FAO in 1999 [ 66 , 67 ]. In addition, for some mycotoxins, this figure may greatly underestimate the occurrence above the detectable levels.…”
Section: Distribution Of Mycotoxins Worldwide—new Risk Maps Due Tomentioning
confidence: 99%